Implementasi Peraturan Menteri Dalam Negeri Republik Indonesia Nomor 1 Tahun 2016 Tentang Pengelolaan Aset Desa - Sofyan Efendi (Jurnal Empirika, 2018)
The problem of village asset management is a problem that often occurs at villages in Indonesia. The basis of this study was on the implementation of the Minister of Home Affairs Regulation no. 1 Year 2016 About Village Asset Management in Bakung Village, Ogan Ilir Regency. The village asset management is divided into three aspects: management and planning of village assets, utilization and security of village assets, and the elimination, alienation and administration of village assets. The policy implementation approach used is from Merilee S. Grindle theory which divides the successful implementation of a policy that can be viewed from two sides: content of policy and context of implementation. The entire research was conducted in a descriptive qualitative research scheme with data analysis techniques using interactive models from Miles and Huberman The findings of the study found that the forms of village asset management efforts conducted in Bakung Village of Ogan Ilir Regency were not in accordance with the concept of Law and Implementation of the Minister of Home Affairs Regulation no. 1 Year 2016 About Village Asset Management in Bakung Village, Ogan Ilir Regency which has not been successful. In a review of the implementation theory of Merilee S. Grindle for the content of policy dimension, there were still many implementers and policy targets that did not understand the content, purpose and objectives of the Minister of Home Affairs Regulation no. 1 Year 2016 About Village Asset Management. Meanwhile, the context of implementation of the inhibiting factor found was that there had not been too many efforts made by the regency government in implementing this regulation.